2018
DOI: 10.1111/jomf.12518
|View full text |Cite
|
Sign up to set email alerts
|

Motherhood, Employment, and Life Satisfaction: Trends in Germany Between 1984 and 2015

Abstract: Objective: This article analyzes trends in the relationships among motherhood, employment, and life satisfaction in Germany and regresses them on changing motherhood norms. Background: Motherhood norms have changed in recent decades in Germany, and differences in labor force participation between mothers and women without children have decreased. We research whether differences in life satisfaction have decreased at the same time. Method: Analyses are based on the German Socio-Economic Panel (1984 and restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
3
11
0
1
Order By: Relevance
“…As each HPRM covers a time span of seven years, the within effects are estimated for women and men with children of up to six years of age compared to their lives up to six years before the transition to parenthood. To estimate the HPRM, all predictors are transformed to a demeaned variable to estimate the within effect and a mean constant variable to estimate the between effect separately for each seven-year panel (see Preisner et al 2018). Finally, we plot the within and between effects derived from the HPRMs over time and correlate the respective effects with parenthood norms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As each HPRM covers a time span of seven years, the within effects are estimated for women and men with children of up to six years of age compared to their lives up to six years before the transition to parenthood. To estimate the HPRM, all predictors are transformed to a demeaned variable to estimate the within effect and a mean constant variable to estimate the between effect separately for each seven-year panel (see Preisner et al 2018). Finally, we plot the within and between effects derived from the HPRMs over time and correlate the respective effects with parenthood norms.…”
Section: Methodsmentioning
confidence: 99%
“…Control variables were carefully selected on the basis of previous research on the relationship between parenthood and life satisfaction in Germany (Myrskylä and Margolis 2014; Pollmann-Schult 2014; Preisner et al 2018; Schröder 2018; Stanca 2009). They match at least one of the following criteria: first, the factor is relevant for the life satisfaction of parents and nonparents; second, it is unequally distributed between German parents and nonparents, as well as between women and men; and/or third, a change has occurred in these resources over the last decades.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are of course many different institutional reasons why the relationship between parenthood and subjective well-being may differ across countries. These could be the extent to which parenthood is chosen, the institutions that determine the degree of work and family reconciliation (Le Moglie et al, 2019), social norms regarding mothers working (Preisner et al, 2018) or family allowances and formal child-care (Pollmann-Schult, 2018). We here suggest that the individuallevel reported degree of financial difficulty plays a role as well.…”
Section: Difficulties Paying Bills and Happinessmentioning
confidence: 99%
“…Research has shown that lack of a suitable partner is a common reason for many to postpone their childbearing, potentially leading to permanent childlessness ( Kapitany and Speder, 2012 , Mynarska, 2010 ). However, recent research shows that other variables such as career advancement, labour market conditions and financial stability are increasingly associated with childlessness in many European countries ( Greulich, 2018 , Koert and Daniluk, 2017 , Kreyenfeld and Konietzka, 2017 , Preisner et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%